THE IMPORTANCE OF LIPOPROTEIN (A) TESTING WITH CASCADE SCREENING FOR FAMILIAL HYPERCHOLESTEROLEMIA (FH) IN YOUNG ADULTS WITH STATIN-RESISTANT HYPERLIPIDEMIA AT RISK FOR EARLY MAJOR ADVERSE CARDIAC EVENTS (MACE) - Jamal A Anthony; Tatiana Echeverry; Robert D Fishberg (American Journal of Preventive Cardiology, 2023)
Therapeutic Area: ASCVD/CVD Risk Assessment Background: FH affects 1:250 and Lp(a) ≥300 nmol/L affects 1:50 individuals; each associated with ∼3x risk of MACE according to the SAFEHEART trial. Furthermore, the combination of both FH and elevated Lp(a) was associated with >4x risk of MACE. In the FOURIER trial, PCSK9 inhibition was shown to reduce MACE by 16%. A sub-study revealed a 23% reduction when Lp(a) is above the mean. We present a patient with genetically confirmed FH and elevated Lp(a) levels >95th percentile, presenting with premature MI and treated with a PCSK9 inhibitor. Methods: A 47-year-old African American male with a history of hyperlipidemia and CAD s/p stenting to the LAD at age 33, presented with a STEMI. He had an acute occlusion of the LAD and a chronically occluded RCA. LDL was 384mg/dL and Lp(a) was 365nmol/L on high dose rosuvastatin. He started Evolocumab 3 days post STEMI. A strong family history of early MACE was present; his mother was on Evolocumab. Genetic testing for LPA gene variants and FH was done. Results: Genetic testing revealed: pathologic LDLR mutation rs577934998 and LP(a) mutation rs9457951 which is commonly found in African Americans. 5-month follow up: Figure 1. Patient has had no recurrence of MACE. He was enrolled in the FH Cascade Registry and invited into the Lp(a)HORIZON trial using TQJ230, Lp(a)-reducing anti-sense agent, but declined. Conclusion: Based on the SAFEHEART study, we conclude that this patient had increased risk of MACE due to his resistant hyperlipidemia and very elevated Lp(a). Therefore, we recommend Lp(a) testing in patients with FH to identify higher risk individuals. As suggested by the FOURIER sub-study, early treatment with a PCSK9 inhibitor should substantially reduce his risk of another event. However, his LDL and Lp(a) are still elevated, and he may still be at risk of a future event. Treatment with novel investigational agents like TQJ230 (which reduces Lp(a) up to 80%) should be considered in such cases. Furthermore, cascade screening for both FH and Lp(a) of first and second-degree relatives should be actively pursued to identify other individuals at high risk who may benefit from aggressive primary prevention with these novel agents.